Women and finance in rural and urban Sudan: A case study in Greater Omdurman and Khartoum - Ulrike Schultz; Asia Makkawi; Tayseer El Fatih (Humboldt-Universität zu Berlin, Wirtschafts- und Sozialwissenschaften an der Landwirtschaftlich-Gärtnerischen Fakultät, 2008)
In the paper it is inquired how Sudanese women use the financial institutions in order to organise their lives between market, household, and the community. The results are based on interviews and observations done in two villages in the surroundings of Omdurman (Al Gharaza and Sanahir), displaced areas in Greater Khartoum (Ha Yusif and Umbedda) and in a lower middle-class area in Omdurman (Thawra). Within a gender ideology that enforces the role of the male provider and the female housekeeper, women seem to have some room of manoeuvre. Most of the interviewed women had access to money, could in some cases dispose of substantial savings and had quite a considerable influence within the household financial decision making. Income earning can widen up the financial repertoire of female behaviour, which, in turn, has led to a challenging of the prevailing conceptualisation of the gendering roles but at the same time questions the male obligation to provide for his family. Within an ongoing process of changing gender roles and expansion of the market economy, women use financial institutions to defend their access to resources and gain new economic power. In this context, women are open-minded about using formal institution such as banks, however, because of high transaction costs and limited trust in the efficiency of these institutions women prefer financial institutions that are embedded in their social networks and daily practices. Microcredit can be a means to enhance women's financial room of manoeuvre. – – In dem vorliegenden Forschungsbericht wird untersucht, wie sudanesische Frauen Finanzinstitutionen nutzen, um ihr Leben zwischen Markt, Haushalt und der Community zu organisieren. Die Ergebnisse basieren auf Interviews und Beobachtungen in zwei Dörfern in der Nähe Khartums, in Migrantenvierteln in Khartum und Omdurman und einem Mittelschichtsviertel in Omdurman (Tharwa). Im Rahmen einer Ideologie, die den Mann als Versorger der Familie und die Frau als Hausfrau definiert, haben Frauen gewisse Handlungsspielräume. Die meisten Frauen haben Zugang zu Geld, verfügen in einigen Fällen über beträchtliche Ersparnisse und beeinflussen die finanziellen Entscheidungen innerhalb des Haushaltes. Eigenes Einkommen kann diese Handlungsspielräume erweitern und die vorgegebenen Geschlechterrollen, damit aber auch die männliche Versorgerrolle in Frage stellen. Innerhalb dieses Prozesses der Veränderung von Geschlechternormen versuchen Frauen, sich neue Räume anzueignen, gleichzeitig traditionelle Rechte und den Zugang zu Ressourcen zu verteidigen und die Männer auf ihre (traditionelle) Versorgerrolle zu verpflichten. Dazu nutzen sie die ihnen zur Verfügung stehenden Finanzinstitutionen und sind auch formellen Institutionen wie Banken gegenüber aufgeschlossen; allerdings wird ihnen der Zugang zu diesen durch hohe Transaktionskosten erschwert. Auch Mikrokreditprogramme werden von den Frauen genutzt und ihren Bedürfnissen entsprechend angeeignet.
Keywords: 330; Sudan; Rural Finance; Microfinance; Women in the Informal Sector; Moral Economy; Female Economy; Poverty Alleviation; Sudan; Ländliche Finanzsysteme; Mikrofinanz; Frauen im informellen Sektor; Moralökonomie; Frauenökonomie; Armutsbekämpfung